Analisis Tingkat Kecemasan Matematika pada Siswa Kelas IX SMP St. Bellarminus Bekasi dan Faktornya dari Sudut Pandang Neurosains - Dyastika, Patricia Agrivina; Usdinoari, Carolina Omega Putri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to analyze 9th graders’ level of mathematics anxiety at St. Bellarminus Bekasi Junior High School and the causes of mathematics anxiety from neuroscience point of view. The method that was used in this research was descriptive research with quantitative approach. The level of mathematics anxiety data was collected by distributing questionnaires that contained 20 statements, and the causes of mathematics anxiety data were collected by literatures review. The mathematics anxiety level was observed from three aspects which are cognitive, affective, and physiological; and would be categorized as low, medium, and high. From the result of this study, it was found that the level of mathematics anxiety in general is categorized as medium, with the percentage is 62%. Students experience the most anxiety in terms of cognitive and the most common symptom experienced by students is headaches. From the neuroscience point of view, the cognitive mathematics anxiety is affected by prefrontal cortex and amygdala hyperactive;the affective mathematics anxiety is affected by the position of prefrontal cortex, left brain hemisphere, and right brain hemisphere; and the physiological mathematics anxiety is affected by the amygdala